Genetic Elimination of eNOS Reduces Secondary Complications of Experimental Subarachnoid Hemorrhage. Issue 7 (July 2013) - Sabri, Mohammed; Ai, Jinglu; Lass, Elliot; D'abbondanza, Josephine; Macdonald, R Loch
Delayed complications of subarachnoid hemorrhage (SAH) such as angiographic vasospasm, cortical spreading ischemia, microcirculatory dysfunction, and microthrombosis are reported in both patients and animal models of SAH. We demonstrated previously that SAH is associated with increased oxidative stress in the brain parenchyma, and that this correlates with dysfunction of endothelial nitric oxide synthase (eNOS) (homodimeric uncoupling). Uncoupling of eNOS exacerbated oxidative stress and enhanced nitric oxide (NO) depletion, and was associated with multiple secondary complications such as microthrombosis, neuronal apoptosis, and release of reactive oxygen species. Thus, we hypothesized that genetic abbrogation of eNOS would confer a beneficial effect on the brain after SAH. Using a prechiasmatic injection model of SAH, we show here that eNOS knockout (KO) significantly alleviates vasospasm of the middle cerebral artery and reduces superoxide production. Endothelial nitric oxide synthase KO also affected other nitric oxide synthase isoforms. It significantly increases neuron nitric oxide synthase expression but has no effect on inducible nitric oxide synthase. Endothelial nitric oxide synthase KO decreases Zn 2+ release after SAH, reduces microthrombi formation, and prevent neuronal degeneration. This work is consistent with our findings where, after SAH, increased oxidative stress can uncouple eNOS via Zn 2+ thiolate oxidation, or theoretically by depletion or oxidation of tetrahydrobiopterin, resulting in a paradoxical release of superoxide anion radical, further exacerbating oxidative stress and microvascular damage.